Preliminary numerical simulation of mirror seeing for the Chinese Future Giant Telescope. (June 2016) - Zhang, En-Peng; Cui, Xiang-Qun; Li, Guo-Ping; Zhang, Yong; Shi, Jian-Rong; Zhao, Yong-Heng
Abstract: Mirror seeing will be one of the key factors influencing image quality of an extremely large ground-based optical telescope (ELT). Computational fluid dynamics (CFD) can be used to estimate the mirror seeing and the effects of ventilation. In this paper, we present a simplified approach to simulation of mirror seeing for the Chinese Future Giant Telescope (CFGT, 30 m in diameter) with the CFD software ANSYS Icepak. We get the FWHM of the image and the distribution of refractive index structure function ( C 2 N ) above the mirror. We demonstrate that thermal control and ventilation are effective ways to improve the image quality. Our simulation results agree with those of other authors for the ELT. To reduce the mirror seeing to a level of 0.5″, the suggested temperature excess of the primary mirror above the ambient air for thermal control of the CFGT is 0 – 2 K according to the present results of weakly forced convection. The limitations of the method are also discussed.